A transformation strategy for Protective Workshops : towards comprehensive services for adults with intellectual disability - Terreblanche, Susan Elizabeth (Stellenbosch : Stellenbosch University, 2015)
Thesis (MOccTher)--Stellenbosch University, 2015.